Commonwealth Transformation Through Christian Community Development. - Dorrell, Jimmy M. (Baylor University Press, 2020)
"Outlines the traditional biblical and theological understanding of wealth, and issues a call for urban mission and reconciliation through examples taken from the work of Mission Waco"--